The winter of red snow : the Revolutionary War diary of Abigail Jane Stewart - Gregory, Kristiana (New York : Scholastic Inc., 1996)
Eleven-year-old Abigail presents a diary account of life in Valley Forge from December 1777 to July 1778 as General Washington prepares his troops to fight the British.
Wilson's Junior High School
School Library Journal
Book Links (A.L.A.)
4.8
5-8
Keywords: United States -- History -- Revolution, 1775-1783 -- Juvenile fiction; Valley Forge (Pa.) -- Fiction; United States -- History -- Revolution, 1775-1783 -- Fiction; Diaries -- Fiction; Valley Forge (Pa.) -- Fiction; United States -- History -- 1775-1783, Revolution -- Fiction